2018
DOI: 10.1016/j.fluid.2017.12.036
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic study of binary systems containing sulphur dioxide and nitric oxide: Measurements and modelling

Abstract: density and osmotic pressure predictions. We then studied the evolution of Henry constant values for gases in brines considering various salt concentrations and temperatures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 86 publications
1
15
0
Order By: Relevance
“…296 (Crozier and Yamamoto, 1974;Gerecke and Bittrich, 1971;Gordon et al, 1977;Morrison and Billett, 1952;Steiner, 1894) (Abascal and Vega, 2005) and the OPLS model for Na þ and Cl À (Chandrasekhar et al, 1984) is selected. The TIP4P/2005 model is able to accurately reproduce pure water density and vapor pressures, and it has been shown in a recent study (Creton et al, 2018) that its combination with the OPLS model for ions allows to reproduce correctly densities and osmotic pressures of aqueous NaCl solutions over a large temperature and salinity range. Details of these molecular models are given in Table 3.…”
Section: Force Fieldmentioning
confidence: 99%
See 1 more Smart Citation
“…296 (Crozier and Yamamoto, 1974;Gerecke and Bittrich, 1971;Gordon et al, 1977;Morrison and Billett, 1952;Steiner, 1894) (Abascal and Vega, 2005) and the OPLS model for Na þ and Cl À (Chandrasekhar et al, 1984) is selected. The TIP4P/2005 model is able to accurately reproduce pure water density and vapor pressures, and it has been shown in a recent study (Creton et al, 2018) that its combination with the OPLS model for ions allows to reproduce correctly densities and osmotic pressures of aqueous NaCl solutions over a large temperature and salinity range. Details of these molecular models are given in Table 3.…”
Section: Force Fieldmentioning
confidence: 99%
“…Previous studies have demonstrated the ability of Monte Carlo simulation to predict gas solubility in brines, such as CO 2 (Creton et al, 2018;Jiang et al, 2017;Liu et al, 2013;Tsai et al, 2016;Vorholz et al, 2004), H 2 S (Fauve et al, 2017), SO 2 and other diatomic light gases (Creton et al, 2018). However, to the best of our knowledge, no molecular simulation study dealing with the solubility of hydrogen in electrolyte solutions has been published.…”
Section: Introductionmentioning
confidence: 99%
“…The variation of the osmotic pressure and density of NaCl with the salinity obtained with our DPD electrolyte model can be observed in Figure a,b, respectively, and compared with the experimental data. , We also compare our results with literature data including atomistic simulations using polarizable FF (PFF) ,,, and nonpolarizable FFs …”
Section: Resultsmentioning
confidence: 59%
“…Our DPD model presents a MARD of 1.0% with respect to the experimental density when the concentration of NaCl is increased in the range of 0–3 m (3% for the range between 3 and 5 m ) as can be seen in Figure b. Usually, all other atomistic models (polarizable and non-polarizable models) tend to underestimate the experimental density, with the exception of the flexible SPCFw model for water (see section 9 of the Supporting Information for details) and the couple of TIP4P-2005 model for water and Reif model for ions . Overall, the present electrolyte DPD model is able to reproduce the variation of the osmotic pressure and density of aqueous solution of NaCl in the whole range of solubility with an accuracy that is equivalent to other more complex, time-consuming atomistic simulations.…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation